Composition-tunable ZnxCd1-xSe nanocrystals with high luminescence and stability - Zhong, Xinhua (2012)
High-quality ZnxCd1-xSe nanocrystals have been successfully prepared at high temperature by incorporating stoichiometric amounts of Zn and Se into pre-prepared CdSe nanocrystals. With increasing Zn content, a composition-tunable emission across most of the visible spectrum has been demonstrated by a systematic blue-shift in emission wavelength. The photoluminescence (PL) properties for the obtained ZnxCd1-xSe nanocrystals (PL efficiency of 70−85%, fwhm = 22−30 nm) are comparable to those for the best reported CdSe-based QDs. In particular, they also have good PL properties in the blue spectral range. Moreover, the alloy nanocrystals can retain their high luminescence (PL efficiency of over 40%) when dispersed in aqueous solutions and maintain a symmetric peak shape and spectral position under rigorous experimental conditions. A rapid alloying process was observed at a temperature higher than “alloying point”. The mechanism of the high luminescence efficiency and stability of ZnxCd1-xSe nanocrystals is explored.